2017
DOI: 10.3389/fpls.2017.00440
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungus Rhizophagus irregularis Increased Potassium Content and Expression of Genes Encoding Potassium Channels in Lycium barbarum

Abstract: Potassium in plants accounts for up to 10% dry weight, and participates in different physiological processes. Under drought stress, plant requires more potassium but potassium availability in soil solutes is lowered by decreased soil water content. Forming symbiosis with arbuscular mycorrhizal (AM) fungi not only enlarges exploration range of plant for mineral nutrients and water in soil, but also improves plant drought tolerance. However, the regulation of AM fungi on plant root potassium uptake and transloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 70 publications
(98 reference statements)
6
42
0
1
Order By: Relevance
“…Plant biomass production is the most obvious trait reflecting plant performance under abiotic stress and the symbiosis efficiency of AM fungi ( Evelin et al, 2009 ; Ruiz-Lozano et al, 2012 ; Porcel et al, 2016 ; Zhang et al, 2017 ). In the present study, although the dry masses of the shoots and roots of both NM and AM plants were reduced by salt stress, AM plants grew better than NM plants at all salinity levels, which suggests that the AM symbiosis mitigated salt stress in black locust and indicates a high symbiosis efficiency of R .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant biomass production is the most obvious trait reflecting plant performance under abiotic stress and the symbiosis efficiency of AM fungi ( Evelin et al, 2009 ; Ruiz-Lozano et al, 2012 ; Porcel et al, 2016 ; Zhang et al, 2017 ). In the present study, although the dry masses of the shoots and roots of both NM and AM plants were reduced by salt stress, AM plants grew better than NM plants at all salinity levels, which suggests that the AM symbiosis mitigated salt stress in black locust and indicates a high symbiosis efficiency of R .…”
Section: Discussionmentioning
confidence: 99%
“…They are two major mechanisms that maintain low Na + accumulation in the cytosol ( Deinlein et al, 2014 ). Moreover, class I HKT transporters are involved in removing Na + from the xylem in order to prevent Na + from transport to the leaves ( Sunarpi et al, 2005 ; Davenport et al, 2007 ), while the outward-rectifying K + channel SKOR controls K + loading into the xylem and K + transport to shoots ( Zhang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A relação entre parte aérea é um atributo importante para plantas superar condições de estresse, como a falta de água. Plantas que com menor relação entre parte aérea e raiz geralmente são mais tolerantes ao estresse por falta de água (XUE et al, 2017;ZHANG et al, 2017 -----------------------------------g vaso -1 ------------------------- Apesar de seu uso difundido nos últimos anos, o efeito de produtos bioestimulantes precisa ser melhor compreendido. Na literatura há resultados divergentes sobre a resposta dos bioestimulantes.…”
Section: Resultsunclassified
“…The promotion of plant nutrient uptake by AMF has received considerable attention over several decades, and the regulation and control mechanisms have been partially determined [46,66,67]. Evidence has shown that AMF could improve the uptake of P [4,32], nitrogen [66], potassium [66], calcium, magnesium, and trace elements, and could contribute to about 70-80% of the P absorbed by hosts.…”
Section: Effects On Plant Growth and Developmentmentioning
confidence: 99%